Development of Transgenic Sugarcane Resistant to Stem Borer by Transforming cry1Ab-cry1Ac Fusion Gene through Agrobacterium tumefaciens Transformation Method - Deden Sukmadjaja; Sri Koerniati; Auliya Lukman (Jurnal AgroBiogen, 2021)
Bulu Lawang (BL) is a sugarcane variety preferred by farmers in Indonesia due to its high yield, but this cultivar is susceptible to shoot and stem borer insect pests. Genetic engineering using cry1Ab and cry1Ac fusion gene is an effort to generate BL varieties resistant to the insect pests. This study aimed to 1) transform T-DNA containing cry1Ab-cry1Ac fusion gene into sugarcane genome by using Agrobacterium tumefaciens method, 2) obtain selection media composition of callus transformants, and 3) obtain transformation efficiency comparison of A. tumefaciens strains EHA105 and GV3101. The research was conducted at the Laboratory of Cell and Tissue Biology, the Laboratory of Molecular Biology, and the greenhouse of the Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development, Bogor from March to August 2019. Research activities consisted of four parts namely 1) callus induction and Agrobacterium culture preparation containing pCambia-5300_OaRbcS-prom-cTP-cry1Ab-cry1Ac plasmid, 2) callus incubation in cocultivation and resting media, 3) selection and differentiation of shoots on regeneration media, and 4) molecular analysis using PCR method. Results showed that the composition of media, both for selection and regeneration processes of putative plant transformants, was the key to the success of this experiment. A. tumefaciens strain EHA105 resulted in higher transformation efficiency (11.1%) compared to that of strain GV3101 (9.0%). Molecular analysis showed that cryIAb-cryIAc fusion gene was successfully inserted into the sugarcane genome suggesting that the transgenic plant containing cry1Ab-cry1Ac fusion gene was obtained. The putative transgenic plants need further assay through bioassay tests to verify its resistance phenotype to the insect pests.